La part salariale dans le revenu national : l’expérience contemporaine - Marion, Gérald; Boury Sy, Aly (L'Actualité économique, 1981)
ABSTRACTIn this paper, we study changes in the wage share that occured during the last thirty-five years. Between 1945 and 1978, the wage share in national income has increased from 64% to 74%. But this increase has not been regular, large cyclical variations are sometimes more important than long run changes. We explained short run variations by the practice of labour hoarding. As to the long run, shift from self-employment to wage and salary earners explained the increase of the wage share and the decrease of the property share. Finally, we test the hypothesis that shifts of sector weights has contributed to this increase.